Terpaan Informasi Hoax McDonald di Whatsapp terhadap Kepercayaan Konsumen - Pramelani Pramelani (Universitas Bina Sarana Informatika, 2018)
Internet users are already getting lots of Indonesia on the population. The most popular application is social media. However, the use of social media is not a bit of the information disseminated. hoax It is experienced by the company McDonald where scattered information in a media hoax promotion McDonald whatsapp. Researchers interested in knowing whether or not there is a relationship of exposure information hoax McDonald on whatsapp against consumer confidence. Then, the determination of the respondent's purposive sampling technique done so obtained 45 samples in areas of Jakarta where never get information on hoaxes whatsapp With quantitative methods using correlation kendall's tau in data processing through the program SPSS version 17.0. The results obtained so that the value of the coefficient correlation research indicated by number of 0.270 meaning there is a close relationship of McDonald's hoax information whatsapp against consumer confidence with a significant level of p = 0.016 < 0.05.